The Tubarial Glands: Key Anatomical Features and Clinical Significance - Nur Aditya, Dwi Martha; Santosa, Winnie Nirmala; Marzuki, Jefman Efendi; Sukarno, Devitya Angielevi; Baharuddin, Baharuddin; Prawitasari, Dita Sukmaya; Sajuni, Sajuni; Setyo Wicaksono, Adhimas; Djuanda, Stephanie Natasha (Folia Medica Indonesiana, 2024)
Medical technological advancements have revealed previously unknown anatomical features in the nasal cavity known as tubarial glands. However, many questions remain unanswered concerning these glands. Through this systematic review, we sought to analyze the tubarial glands, including their major discovery, anatomical and histological features, and clinical significance. Articles were identified according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, with data collected from Scopus, ScienceDirect, SpringerLink, and PubMed until September 2024. Medical Subject Headings (MeSH) were utilized with various terminology: